Optimization of the mechanical strength of PVA/alginate gel beads and their effects on the ammonia-oxidizing activity - Bae, Hyokwan; Yang, Heejeong; Choi, Minkyu; Chung, Yun-Chul; Lee, Seockheon; Yoo, Young Je (DESALINATION PUBL, 2015)
Poly (vinyl alcohol) (PVA)/alginate gel beads were fabricated to entrap ammonia-oxidizing bacteria. The PVA/alginate gel beads were prepared in different conditions to investigate the effects of the fabrication procedures on the mechanical strength and the initial ammonia-oxidizing activity. For the mechanical strength, the optimal conditions were analyzed using response surface analysis (RSA) considering the inter-correlated effects of the reaction times of cross-linking and phosphorylation. For RSA, nine trials resulted in a partial cubic polynomial equation, which best predicted the amount of residual debris after homogenization. In the model, the optimum conditions of 3.5 h of cross-linking and 5.6 h of phosphorylation were estimated to ensure the maximum mechanical strength. The initial ammonia-oxidizing activity was significantly affected by the cross-linking due to the highly acidic environment of pH 3.3, but it was not affected by the phosphorylation in pH 4.2. Batch experiments to measure the bioactivity showed that only 34.0% of the initial activity survived the fabrication procedure of the 4 h reaction in B(OH)(3) in comparison to the 1 h reaction. The lower initial ammonia-oxidizing activity contributed to the delayed acclimation period to achieve ammonia removal of more than 1 kg N/m(3) d, but the inhibitory effects were fully recovered in 5 d.
Keywords: WASTE-WATER TREATMENT; CELL IMMOBILIZATION; NITRIFICATION; BACTERIA; COMMUNITY; KINETICS; REACTORS; NITROGEN; REMOVAL; ACID